2007
DOI: 10.1002/j.1556-6978.2007.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Counselor Education Programs Promote Wellness in Their Students?

Abstract: It is widely accepted that counselor impairment presents a problem in the counseling profession (M. E. Young & G. W. Lambie, 2007). Wellness as a unifying philosophy in counselor education may be a way to prevent impairment and burnout in students and professionals. Although counselor educators strive to promote a wellness philosophy in students, their efforts may be largely unsuccessful. This study examines the influence of counselor education programs on counselor wellness by investigating broad trends in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 39 publications
6
93
3
1
Order By: Relevance
“…For counselors, self-awareness is particularly important for practice (Williams, Hayes, & Fauth, 2008). Similar to some of the participants in this study, personal counseling and other wellness strategies appeared to be beneficial for overall functioning and self-efficacy (Hermon & Hazler, 1999;Prosek, Holm, & Daly, 2013;Roach & Young, 2007). This is consistent with a study by Ruggerio, Rabino, Richards, and Martin (2013) who found that students who experienced increased self-knowledge and compassion also had increased levels of counseling self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For counselors, self-awareness is particularly important for practice (Williams, Hayes, & Fauth, 2008). Similar to some of the participants in this study, personal counseling and other wellness strategies appeared to be beneficial for overall functioning and self-efficacy (Hermon & Hazler, 1999;Prosek, Holm, & Daly, 2013;Roach & Young, 2007). This is consistent with a study by Ruggerio, Rabino, Richards, and Martin (2013) who found that students who experienced increased self-knowledge and compassion also had increased levels of counseling self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…Graduate student persistence was reported to be higher in students with supportive partners, children, and parents (Cohen & Greenberg, 2011). The strength of the relationships with family is significant to counseling students as it can reduce stress (Mallinckrodt & Leong, 1992;Roach & Young, 2007) and promote stamina in practice post-graduation (Freadling & Foss-Kelly, 2014 (Roach & Young, 2007). For example, activities like meditation have been found to help clinicians self-nurture, manage stress, and maintain social connectedness (Boellinghaus, Jones, & Hutton, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clients get to do whatever they want…" Other participants faced stressors related to learning the site processes and procedures. Graduate students often have a complicated balance of family, work, and academic pressures to navigate (Hyun, Quinn, Madon, & Lustig, 2006;Lenz, Sangganjanavanich, Balkin, Oliver, & Smith, 2012;Roach & Young, 2007;Smith, Robinson, & Young, 2007). Reaching the field placement milestone in a counselor education program brings excitement, uncertainty, and apprehension.…”
Section: Discussionmentioning
confidence: 99%